Clinical Review: Emergency management of acute poisoning - D.J. van Hoving; D.J.H. Veale; G.F. Müller (African Journal of Emergency Medicine, 2011)
Acutely poisoned patients are commonly encountered in Emergency Centres. Acute poisoning (accidental or intentional) requires accurate assessment and prompt therapy. The necessity to prevent cross contamination during the initial evaluation should be emphasized. Early identification of the involved toxin/s is crucial and the majority will be identified by a thorough history and physical examination. An ABC-approach should be followed ensuring a protected airway, adequate ventilation and hemodynamic stability. Supportive and symptomatic care remains the cornerstone of treatment. A stepwise approach may be followed to decrease the bioavailability of toxins. Indications, contra-indications, risks and dosage regimens are describe for decontamination procedures including both termination of topical exposures and decreasing exposure to ingested toxins. Furthermore, procedures to increase the elimination of toxins and a short section covering specific toxins and their antidotes are also included. The aim of this commissioned review was to establish concise guidelines for the initial management of the acutely poisoned patient in the Emergency Centre. The American Academy of Clinical Toxicology and the European Association of Poisons Centres and Clinical Toxicologists are the international leaders in the field of toxicology and the guidelines in their position papers were generally followed. Most of the dosage regimes are according to the South African Medicines Formulary.